Expression and mutational analysis of Nm23-H1 in liver metastases of colorectal cancer. - Heide, I. (Nature Publishing Group, 1994)
It has been proposed that nm23-H1, a candidate suppressor gene for metastasis, plays an important role in metastasis formation of human tumours. In order to investigate its role in the progression of colorectal cancer, we analysed 22 liver metastases of this malignancy with respect to mutational changes, loss of heterozygosity and expression levels of nm23-H1. Although genetic alterations in nm23-H1 have recently been described in those colorectal adenocarcinomas which give rise to distant metastases, we were unable to detect any mutation in the coding sequence of nm23-H1 in the metastatic tissue itself. We further analysed the metastases with respect to allelic deletions at the chromosomal locus of nm23. However, no loss of heterozygosity could be detected in ten informative cases. Moreover, the mRNA expression levels of nm23-H1 in the metastatic tissues were not significantly different from those in normal colon mucosa. Thus, although nm23-H1 might be involved in metastasis suppression of certain tumour types, in colorectal tumour progression its role remains to be determined. IMAGES: